An automated syringe-based PoC RT-LAMP LFB platform for infectious disease detection from saliva - Naranbat, Dulguunnaran; Murphy, John; Tripathi, Anubhav (Frontiers in Lab on a Chip Technologies, 2024)
Decentralized Point-of-Care (PoC) diagnostics hold momentous potential for rapid and accessible viral infection disease detection. Presented is a unique design application of an easy-to-use (plugand-play) platform for viral detection. The platform leverages a simplified multiplex Reverse-Transcription Loop-mediated Isothermal Amplification (RT-LAMP) Lateral Flow Biosensor (LFB) assay with a lyophilized master mix, eliminating the need for RNA isolation or special reporting equipment. A user-friendly Saliva Measuring Tube (SMT) ensures accurate saliva volume self-collection, and a Syringe-based PoC (SPoC) platform automates sample treatment, reagent mixing, and temperature control using readily available components and consumables. The platform's performance was evaluated by multiplexed detection of the SARS-CoV-2 N2 target gene and human ACTB gene from saliva samples. The SPoC platform achieved a detection limit of spiked 500 copies/mL for SARS-CoV-2 and consistent internal control readout. The presented PoC system offers a promising initial step for further development toward a decentralized solution for viral infection testing.